Football team for the Montezuma Mountain School for Boys - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Panormaic view of the Montezuma Mountain School for Boys football team and coaches. In center one young male holds the football with 1934 recorded in white. In the background is the school grounds, which includes a large Spanish-style building on the right, and to the left are other campus buildings.